Break out - Kaplan, Zack (Dark Horse Books, 2022)
"Mysterious and massive cube spaceships from another dimension materialize over our cities around the globe. They routinely abduct teenagers to be held inside their floating prison ships. And the world accepts it as inevitable. But not Liam Watts. His younger brother has been taken. And Liam is tired of "thoughts and prayers". Now, in a "take back our future" anthem, Liam must assemble a skilled team of ordinary high school students and in just a few weeks, they must plan a heist to infiltrate a hi-tech prison ship a mile in the sky. But what they'll find there will throw their plans into turmoil and challenge their resolve. How do you break out of a prison that's not even from this world?"--